2022
DOI: 10.3390/ijms232213798
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Indicators of Blood-Brain Barrier Breakdown and Neuronal Injury in Pregnancy Complicated by Fetal Growth Restriction

Abstract: This study evaluated the damage to the endothelial tight junctions (TJs) in pregnancies complicated by fetal growth restriction (FGR) and investigated whether FGR is related to blood–brain barrier disintegration and, subsequently, to the appearance of proteins indicative of neuronal injury in maternal blood. The studied group included 90 pregnant women diagnosed with FGR. The control group consisted of 70 women with an uncomplicated pregnancy. The biochemical measurements included serum neuronal proteins (subu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…In contrast, Misan et al. reported that ZO-1 levels in both serum and placentas showed no significant difference between IUGR and control groups ( 75 ). Although recent study findings suggest that ZO-1 participates in the trophoblast syncytialization process, there is not sufficient evidence to prove that the occurrence of IUGR is related to the syncytialization deficiency caused by abnormal expression of ZO-1, which may be a new direction for future research.…”
Section: Syncytialization-related Proteinsmentioning
confidence: 90%
“…In contrast, Misan et al. reported that ZO-1 levels in both serum and placentas showed no significant difference between IUGR and control groups ( 75 ). Although recent study findings suggest that ZO-1 participates in the trophoblast syncytialization process, there is not sufficient evidence to prove that the occurrence of IUGR is related to the syncytialization deficiency caused by abnormal expression of ZO-1, which may be a new direction for future research.…”
Section: Syncytialization-related Proteinsmentioning
confidence: 90%
“…TJ proteins are the main components of tight junctions between the brain endothelial cells that are crucial to maintaining BBB integrity. Previous studies have shown that these proteins are present in patients with BBB disruption [40][41][42][43]. One study [43] found that OCLN expression in the brain vascular endothelium was significantly higher than in the non-nervous tissue vascular endothelium, which explains why BBB permeability is significantly lower than in other blood tissue barriers.…”
Section: Discussionmentioning
confidence: 99%
“…Misan et al [ 12 ] described the destabilization of the blood–brain barrier in pregnancies complicated by fetal growth restriction. Neurological disorders in newborns, including intraventricular hemorrhage, were associated with higher serum levels of NME1, nucleoside diphosphate kinase A, and the decreased placental expression of CLN4.…”
mentioning
confidence: 99%